5 REASONS BEHIND THE FAILURE OF THE STARTUPS - Habibullayev Samandar; Saidov Sardor; Shavkatxodjayev Rasulxo’ja (Ta’lim innovatsiyasi va integratsiyasi, 2024)
Abstract: This paper explores major causes of startup failures, and common barriers to business success. Although startups are new ventures with great entrepreneurial potential and rate of development, they fail because of weak business models, wrong positioning of products on the market, internal conflicts, lack of finance, and high competition. The paper examines literature and conducts interviews with startup owners and identify some of the problems that plague many start-ups including the focus on product development and the wrong revenue models that may not respond to market needs. Based on real life examples of Quibi, Theranos and Juicero, the study delivers key take-aways and suggested frameworks that focus on robust business models, identifying the right market, building the right team, financial management and developing competitive differentiation to improve startup outcomes.